1979
DOI: 10.1080/15298667991430451
|View full text |Cite
|
Sign up to set email alerts
|

A sampling and analytical method for vinylidene chloride in air

Abstract: A sampling and analytical method for the determination of vinylidene chloride in air is presented. Vinylidene chloride can be quantitatively trapped on charcoal over a wide range of concentrations. The collected vapors are desorbed with carbon disulfide and analyzed by gas chromatography utilizing a flame ionization detector. The analytical column is packed with Durapak OPN. The lower limit for the method is approximately 7 micrograms of vinylidene chloride per sampling tube. The breakthrough volume was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During the summer of 1979, attempts were made at this laboratory to develop a gas-chromatographic procedure for analysis of vinylidene chloride. In the meantime Foerst (5) reported that vinylidene chloride can be analyzed by gas chromatography by using Durapak OPN as an analytical column.…”
Section: Introductionmentioning
confidence: 99%
“…During the summer of 1979, attempts were made at this laboratory to develop a gas-chromatographic procedure for analysis of vinylidene chloride. In the meantime Foerst (5) reported that vinylidene chloride can be analyzed by gas chromatography by using Durapak OPN as an analytical column.…”
Section: Introductionmentioning
confidence: 99%